Immunohistochemical testing of BRAF V600E status in 1,120 tumor tissue samples of patients with brain metastases - Capper, David; Pusch, Stefan; Meyer, Jochen; Habel, Antje; Deimling, Andreas von; Preusser, Matthias (Acta neuropathologica, 2012)
Brain metastases (BM) are frequent and carry a dismal prognosis. BRAF V600E mutations are found in a broad range of tumor types and specific inhibitors targeting BRAF V600E protein exist. We analyzed tumoral BRAF V600E-mutant protein expression using the novel mutation-specific antibody VE1 in a series of 1,120 tumor specimens (885 BM, 157 primary tumors, 78 extra-cranial metastases) of 874 BM patients. In 85 cases, we performed validation of immunohistochemical results by BRAF exon 15 gene sequencing. BRAF V600E protein was expressed in BM of 42/76 (55.3%) melanomas, 1/15 (6.7%) ovarian cancers, 4/72 (5.5%) colorectal cancers, 1/355 (0.3%) lung cancers, 2/6 thyroid cancers and 1/2 choriocarcinomas. BRAF V600E expression showed high intra-tumoral homogeneity and was similar in different tumor manifestations of individual patients. VE1 immunohistochemistry and BRAF exon 15 sequencing were congruent in 68/70 (97.1%) cases, but VE1 immunostaining identified small BRAF V600E expressing tumor cell aggregates in 10 cases with inconclusive genetic results. Melanoma patients with BRAF V600E mutant protein expressing tumors were significantly younger at diagnosis of the primary tumor and at operation of BM than patients with non-mutated tumors. In conclusion, expression of BRAF V600E mutant protein occurs in approximately 6% of BM and is consistent in different tumor manifestations of the same patient. Thus, BRAF V600E inhibiting therapies seem feasible in selected BM patients. Immunohistochemical visualization of V600E-mutant BRAF protein is a promising tool for patient stratification. An integrated approach combining both, VE1 immunohistochemistry and genetic analysis may increase the diagnostic accuracy of BRAF mutation analysis.
Gesehen am 18.04.2018